1992
DOI: 10.1039/c39920000727
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis of polyphenylene in an ionic liquid: the possibility of relative molecular mass regulation

Abstract: An ionic liquid based on aluminum chloride and butylpyridinium chloride has been used as the solvent for the chemical synthesis of poly(p-phenylene).A large number of publications have been devoted to the synthesis and investigation of poly(p-phenylene) (PpP) (see, for example, recent reviews1.2).Ionic liquids are convenient electrolytes for electrochemical synthesis.3 In the present work such a liquid was first used for the oxidative dehydropolycondensation of benzene.The synthesis of BunPyC1 and the ionic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…The systems studied include the polymerization of ethylene with a Ziegler-Natta catalyst [3,4] as well as the application of ionic liquids as polymerization media for the synthesis of polyphenylene. [5] The polymerization of styrene in an ionic liquid leading to conducting ionic liquid-polymer alloys was also reported. [6] Recently, the application of an ionic liquid as the solvent for radical polymerization was described.…”
Section: Introductionmentioning
confidence: 97%
“…The systems studied include the polymerization of ethylene with a Ziegler-Natta catalyst [3,4] as well as the application of ionic liquids as polymerization media for the synthesis of polyphenylene. [5] The polymerization of styrene in an ionic liquid leading to conducting ionic liquid-polymer alloys was also reported. [6] Recently, the application of an ionic liquid as the solvent for radical polymerization was described.…”
Section: Introductionmentioning
confidence: 97%
“…[1,2] Recently, intensive studies have been reported on various types of polymerization in RTILs, [3] such as radical polymerization, [4][5][6][7][8][9][10][11][12][13] ionic polymerization, [14,15] among them controlled/living radical polymerization including atom transfer radical polymerization (ATRP), [5][6][7][8] reversal atom transfer radical polymerization (r-ATRP), [9] reversible addition-fragmentation chain transfer (RAFT) [10,11] and nitroxide-mediated polymerization (NMP). [12,13] In controlled/living polymerization, researchers observed not only a narrow polydisperse product but also a significantly enhanced polymerization rate.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] A variety of structure and function of ionic liquids will control activity, selectivity and stability of catalysis in their use as solvent, yielding production of useful and functional materials. As for polymerizations in ionic liquids, olefin polymerization, 5 oxidative polymerization of benzene to poly(p-phenylene), 6 and copper (I)-mediated living radical polymerization of methyl methacrylate 7 were reported.…”
mentioning
confidence: 99%